2019
DOI: 10.1111/pin.12742
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion‐related extranodal large B‐cell lymphoma: A report of six patients with neoplastic PD‐L1‐positive extranodal diffuse large B‐cell lymphoma

Abstract: We identified six patients with Epstein-Barr virus (EBV)-negative extranodal diffuse large B-cell lymphoma (DLBCL) and immunohistochemical expression of PD-L1 on their tumor cells by examining 283 DLBCL cases with the PD-L1 SP142 clone between 2015 and 2017. They consisted of two men and four women with a median age of 71 years, and were examined in an autopsy (n ¼ 1) and biopsies from the adrenal gland (n ¼ 2), skin (n ¼ 1), pelvic cavity (n ¼ 1), and kidney (n ¼ 1). All showed a monomorphic population of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…Recently, Suzuki et al . reported expression of PD‐L1 on neoplastic cells in extranodal large B cell lymphomas in a series of six cases, five of which showed complete to partial intravascular pattern . In this study, we found that four cases (44.4%) were PD‐L1‐positive.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, Suzuki et al . reported expression of PD‐L1 on neoplastic cells in extranodal large B cell lymphomas in a series of six cases, five of which showed complete to partial intravascular pattern . In this study, we found that four cases (44.4%) were PD‐L1‐positive.…”
Section: Discussionsupporting
confidence: 55%
“…PD‐L1 protein expression (programmed cell death receptor ligand 1) was also found to be more prevalent in extranodal DLBCL disease than the nodal patients 18 . Expression of PD‐L1 protein is linked to poor prognosis in DLBCL patients with extranodal site of disease 19 . Activation of programmed cell death 1 signalling enables DLBCL tumour cells evade from T cell‐mediated immune response, hence, enhances tumour cells survival and promotes disease progression 20 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, PD‐L1 immunostaining highlighted the diffuse extravascular invasion of IVLBCL in the affected organs, begging the question whether neoplastic PD‐L1 expression is associated with either additional genetic alterations or the loss of the intravascular microenvironment. We recently reported a short series of immune escape‐related extranodal large B‐cell lymphoma cases, featuring exclusively extranodal sites, neoplastic PD‐L1 expression, and often a partially intravascular pattern . These data were obtained from biopsy specimens and not autopsy material.…”
Section: Discussionmentioning
confidence: 99%